EVALUASI NILAI CACAT DAN CITA RASA KOPI ROBUSTA (Coffea canephora L.) YANG DIPRODUKSI IKM KOPI DI KABUPATEN TANGGAMUS [Evaluation of Defect Value and Flavour of Robusta Coffee (Coffea canephora L.) Produced by Small and Medium Industry Sector of Coffee in Tanggamus District] - Sri Setyani; Subeki Subeki; Henrica Agustina Grace (Jurnal Teknologi & Industri Hasil Pertanian, 2018)
The purpose of this study was to evaluate the defects, moisture content, flavor, and overall acceptance of Robusta coffee from 20 coffee producers in Tanggamus Regency. Taste testing involved some expert panelists. The data were analyzed descriptively. The results showed that as much as 70% of coffee quality was following SNI 01-2907-2008. The defect value of coffee was at the quality level of 5 until the inferior original quality (“kopi asalan”). The main percentages of the defects were broken seeds, brown beans, black seeds and then followed by hollow seeds. The water content of the coffee was varied between 5.07-7.27.  The taste of coffee was dominated by green/grassy, the average taste was slightly bitter, the colors ranged from brown, black and cinnamon-like color, while, the overall acceptance was somewhat like. This results indicated that standard operating procedure is required to be implemented by coffee producers (IKM) in Tanggamus Regency to improve the quality of the coffee.